The «Son of Man» and the eschatology of the Q beatitudes: the case of Lk 6,22c - Di Luccio, Pino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
In recent research it has been demonstrated that the Aramaic equivalent of «Son of Man» is the translation of אדם ,אנוש ,איש ,אדם נפש ,ב and is thus a normal term for «man». On the contrary, the main occurrences in NT point to a specific, known, individual figure. Taking as a case study Lk 6,22c, this study suggests the hypothesis that when the expression «Son of Man» was introduced into Q beatitudes, it had a messianic meaning, and that it joins together two views of eschatology: an eschatology of the (close) final judgment in addition to the eschatology of the reward in heaven, which may have belonged to an earlier stage of the composition (Lk 6,22ab-23).